Control of Varroa Mite (Varroa destructor) on Honeybees by Aromatic Oils and Plant Materials - I.K. Nazer (Journal of Agricultural and Marine Sciences, 2003)
The effect of several volatile plant oils, plant materials and fluvalinate (Apistan®) strips on the control of the mite Varroa destructor on honeybee (Apis mellifera L.) colonies was studied. The volatile oils were: clove, lavender, peppermint, sage, and thyme. The plant materials were: cumin fruits, eucalyptus leaves, and worm wood flowers. For each tested material, three treatment periods were carried out. Each period lasted for 24 days followed by eight days no-treatment. Within each treatment period, an average of three to six treatments were applied. Dead mites were counted one hour before and after each treatment. An increase in dead mites was recorded for the three treatment periods. It indicated that worm wood flowers, peppermint oil and clove oil treatments gave the best results in the control of Varroa mites but not significantly different than the control. The overall increase in the dead mites was 3.92, 3.62 and 3.34 fold, respectively.